Atomic Scale Materials for Emerging Robust Catalysis. Issue 11 (17th August 2018) - Sun, Xian; Chen, Yunxu; Liu, Keli; Ding, Yu; Zeng, Mengqi; Fu, Lei
Abstract: Atomic scale materials (ASMs) have drawn great interest from researchers in the field of catalysis, due to their novel structures and attractive properties. As a kind of high‐efficiency catalyst, ASMs exhibit massive active sites, fast charge diffusion rates, and maximum atomic utilization, which endow them with a superior catalytic performance. Herein, the current progress in the development of ASMs for core catalytic systems is summarized, which focuses on the distinct structural characteristics and great catalytic advantages of ASMs, as well as their underlying catalytic mechanism for various reactions. Significantly, it is indicated that ASMs are promising catalysts for robust catalysis, which possess high catalytic activity, good selectivity, long‐term stability, excellent poisoning tolerance, and strong conditional adaptability in catalytic applications, and are gradually applied in the field of industrialization. Finally, the opportunities and challenges of ASMs in the field of catalysis are discussed. This review provides a new impetus for the fundamental design and further exploration of catalysts. Abstract : The distinct structural characteristics endow atomic scale material (ASM) catalysts great catalytic advantages, especially the massive active sites, maximum atomic utilization, and fast charge diffusion. ASM catalysts have demonstrated their huge potential in various core catalytic reaction systems. It is envisioned that ASM catalysts will open up a new territory in the field of catalysis.